Tau and amyloid β proteins distinctively associate to functional network changes in the aging brain. Issue 11 (30th March 2017) - Sepulcre, Jorge; Sabuncu, Mert R.; Li, Quanzheng; El Fakhri, Georges; Sperling, Reisa; Johnson, Keith A.
Abstract: Introduction: Misfolded tau and amyloid β (Aβ) proteins progressively accumulate in the human brain, causing altered neuronal function and neurodegeneration. This study sought to investigate whether the wide spectrum of functional reorganization in aging brains of cognitively normal individuals relates to specific pathological patterns of tau and Aβ deposits. Methods: We used functional connectivity neuroimaging and in vivo tau and Aβ positron emission tomography scans to study cortical spatial relationships between imaging modalities. Results: We found that a negative association between tau and functional connectivity combined with a positive association between Aβ and functional connectivity is the most frequent cortical pattern among elderly subjects. Moreover, we found specific brain areas that interrelate hypoconnectivity and hyperconnectivity regions. Discussion: Our findings have critical implications to understanding how the two main elements of Alzheimer's disease–related pathology affect the aging brain and how they cause alterations in large‐scale neuronal circuits. Highlights: Tau deposits dwell in areas of functional hypoconnectivity in the aging brain. Amyloid β (Aβ) deposits tend to overlap with mixed and hyperconnected brain regions. Hypoconnectivity and hyperconnectivity are two interdependent phenomena in the default mode network. Tau and Aβ play characteristic roles in the neuronal breakdown during aging.